Hodnocení finanční situace podniku a návrhy na její zlepšení - Šustrová, Barbora (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Bakalářská práce se zaměřuje na hodnocení finanční situace vybraného podniku za období let 2006 až 2015 s použitím vybraných metod finanční analýzy a poté na návrhy na její zlepšení. První část obsahuje teoretická východiska práce. Popisuje všechny vybrané ukazatele. Druhá praktická část se přímo zabývá vybraným podnikem a analýzou jeho finančního zdraví. Na základě této analýzy budou stanoveny návrhy na zlepšení.

This bachelor thesis focuses on the evaluation of the financial situation of a selected company for the period from 2006 to 2015 using selected methods of financial analysis and then proposals for its improvement. The first part contains theoretical work. It describes all the selected indicators. The second part deals directly with the selected company and analyzing its financial health. Based on the analysis, suggestions for improvement will be determined.
Evaluation of the Financial Situation of a Company and Proposals for its Improvement
Keywords: finanční analýza; rozvaha; výkaz zisků a ztrát; likvidita; rentabilita; SWOT analýza; Altmanova analýza; financial analysis; balance; profit and loss statement; liquidity; profitability; SWOT analysis; Altman Z-score